The effectiveness pictures media on intensive reading course for students’ reading comprehension (Conference on English Language Teaching, 2023)
This research aimed to obtain empirical evidence of the effectiveness of pictures onIntensive Reading Class for Students Comprehension in D3. English Programs UNMERMalang. The objective to find challenges students’ faced in reading skill especially inIntensive Reading class in semester 1 (one). Whether reading skill could be improvedby using pictures. This research is quantitative research by methodology experimentand conducted in two classes. Experimental group class A and control class groupclass B. Class A was taught by using pictures, while class B was not taught by usingpictures. Author gave a reading test to gather the data. The mean of pretest in theexperimental group is 61.37 and the control group is 58.5. The mean of post-test inthe experimental group is 75.03 and the control group is 67.40. The obtained t-test is5.76, whereas the t-table is 2.00 for α = 5%. The t-test value is higher than the t- table(5.76 > 2.00). Based on the result, picture effectiveness improved reading skillstudents in Intensive reading class for students in UNMER Malang. Writer suggests tothe teacher and lectures, especially in reading class, to use pictures as one of themedia in teaching learning for students.